MINAT BELAJAR MATEMATIKA SISWA KELAS V MADRASAH IBTIDAIYAH SWASTA (MIS) DARUSSALAM SUKASLAMET KROYA INDRAMAYU - Abdul Qodir; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2023)
The Achievment of learning outcomes for each student is different, there are several factors both internal and external which affect student’mathematics learning outcome. The purpose of this study is to investigate the factors affecting the fifth graders’ mathematic interest in primary school of (MIS) Madrasah Ibtidiyah Swasta Darussalam Sukaslamet in academic year 2018/2019. This research was a Quatitative study using saturated sampling (census) wihtin all of 17 students in grade 5 are involved. This Quantitative study used correlation methode. The data collected were analyzed using simple linear regression technique product moment correlatin and the coefficient of determination with the help of spss 23 sofware. The result showed that there was not a positive correlation between the students achievment of mathematics learning outcome and their interest in learning mathematics. The significant value of the interest in learning mathematics was obtained 0,381. It was greater than 0,05. And the value of pearson correlation between the mathematics learning interest and the achievement of examination result (Penilaian Akhir Tahun) was-0,227.